Fiscal Implications of Free Education : The Case of Tanzania - Asim, Salman; Chugunov, Dmitry; Gera, Ravinder (World Bank, Washington, DC, 2019)
Tanzania became one of the first low-income countries to abolish fees for lower secondary education (grades 8-12) in 2015. One of the pledges of a new, reformist government, the policy built on the country’s previous experience of abolishing primary fees in 2002. The new Fee-Free Basic Education Policy (FFBEP) extended the abolition of formal fees to lower secondary education, and prohibited both primary and lower secondary schools from levying informal fees, such as for inspections. The introduction of FFBEP has already enabled a large increase in the proportion of students entering primary school, and the proportion transitioning to secondary level. Over the next few years more than a million additional lower secondary places will be required to meet the increase in demand. This rapid expansion of lower secondary education is a boon for access and an important step for Tanzania to achieve its goal of attaining middle-income status by 2025. However, such a pace of expansion poses a significant fiscal challenge. Careful planning is required at this stage to develop a model of lower secondary education which can be scaled up in a sustainable way. In partnership with the government of Tanzania, the authors have developed a simulation model to estimate the fiscal impacts of various policy parameters with relevance to the implementation of FFBEP at lower secondary level. The findings presented in this note are based on the simulation tool developed for use by the government.